2021
DOI: 10.3390/ijms221810020
|View full text |Cite
|
Sign up to set email alerts
|

An Attenuated Targeted-TNF Localizes to Tumors In Vivo and Regains Activity at the Site of Disease

Abstract: Antibody-cytokine fusion proteins (immunocytokines) are gaining importance for cancer therapy, but those products are often limited by systemic toxicity related to the activity of the cytokine payload in circulation and in secondary lymphoid organs. Tumor necrosis factor (TNF) is used as a pro-inflammatory payload to trigger haemorrhagic necrosis and boost anti-cancer immunity at the tumor site. Here we describe a depotentiated version of TNF (carrying the single point mutation I97A), which displayed reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Similar to including point mutations to reduce antibody-mediated toxicity, this technique has also been successfully applied to cytokines [ 145 , 146 ]. These mutated cytokines are referred to as Activation-by-Targeting Cytokines (AcTakines).…”
Section: Current Challenges and Routes Of Future Payload Developmentmentioning
confidence: 99%
“…Similar to including point mutations to reduce antibody-mediated toxicity, this technique has also been successfully applied to cytokines [ 145 , 146 ]. These mutated cytokines are referred to as Activation-by-Targeting Cytokines (AcTakines).…”
Section: Current Challenges and Routes Of Future Payload Developmentmentioning
confidence: 99%
“…Early findings in glioblastoma patients showed that L19-TNF monotherapy could decrease blood perfusion within the tumor, which was associated with increased tumor necrosis and T-cell infiltration [ 67 , 69 ]. Anti-CD13 antibodies have also been used as TNF vehicles [ 70 , 71 ]. An interesting strategy developed to reduce the systemic toxicity of antibody-TNF conjugates is based on the use of conjugates bearing mutations in the TNF moiety that decrease its affinity for TNF receptors, thereby reducing off-target effects on normal cells [ 70 , 71 ].…”
Section: Clinical Studies With Ngr-tnfmentioning
confidence: 99%
“…Anti-CD13 antibodies have also been used as TNF vehicles [ 70 , 71 ]. An interesting strategy developed to reduce the systemic toxicity of antibody-TNF conjugates is based on the use of conjugates bearing mutations in the TNF moiety that decrease its affinity for TNF receptors, thereby reducing off-target effects on normal cells [ 70 , 71 ]. These de-potentiated TNF versions, thanks to their specific accumulation on the target molecules, such as alternatively spliced EDB domain of fibronectin or CD13, can regain their activity on targeted cells, e.g., by local avidity-driven receptor binding.…”
Section: Clinical Studies With Ngr-tnfmentioning
confidence: 99%
See 2 more Smart Citations